2011
DOI: 10.1177/0149206311407509
|View full text |Cite
|
Sign up to set email alerts
|

How Lead Founder Personality Affects New Venture Performance

Abstract: This empirical study of 323 new ventures examines how task and relationship conflict in the founding top management team mediates the effect of lead founder personality on new venture performance. The results reveal that (1) openness and agreeableness increase task conflict, whereas conscientiousness decreases it, and (2) openness, extraversion, and conscientiousness decrease relationship conflict, whereas neuroticism increases it. Furthermore, task conflict increases venture performance, whereas relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 132 publications
(210 reference statements)
8
74
1
Order By: Relevance
“…This supports the previous research and shows that personality characteristics can determine the perception of conflicts (De Jong et al, 2013). Big Five personality traits have helped in personnel selection, training and promotion, and it should be used to determine group composition, conflict management and intervention by superiors and also performance expectations and evaluations.…”
Section: Research and Practical Implicationssupporting
confidence: 89%
See 2 more Smart Citations
“…This supports the previous research and shows that personality characteristics can determine the perception of conflicts (De Jong et al, 2013). Big Five personality traits have helped in personnel selection, training and promotion, and it should be used to determine group composition, conflict management and intervention by superiors and also performance expectations and evaluations.…”
Section: Research and Practical Implicationssupporting
confidence: 89%
“…Research literature is, however, lacking regarding a link between conflict and performance (Rahim, 2000;Shih and Susanto, 2010). De Jong et al (2013) observed that conflict partially mediates the relationship between personality and performance. We speculate that CMSs introduced as a moderator of the conflict to performance link will explain the mediating role of conflict in the personality to performance relationship.…”
Section: H2 Extraverts Conscientious and Open People Will Have An Amentioning
confidence: 99%
See 1 more Smart Citation
“…De Jong, Song, and Song (2013), for example, examines the relations among lead founder personality, task conflict, relationship conflict, and new venture performance.…”
Section: Ceo-tmt Interfacementioning
confidence: 99%
“…In Part B, respondents answer questions assessing their personality traits and team climate variables that were predicted to relate to innovation (though the latter were omitted from analysis (Baer & Frese, 2003;de Jong et al, 2011;Eisenbeiss et al, 2008;Gong et al, 2012;Kim et al, 2009;Moore, 2006;Ogawa, 1998;Ohly & Fritz, 2007;Sasovova et al, 2010;Somech & Drach-Zahavy, 2011;Zhou, 2003).…”
Section: Part B: Personality Traitsmentioning
confidence: 99%